Multiple concurrent collagenase clostridium histolyticum injections to dupuytren’s cords: an exploratory study - Coleman Stephen (BMC Musculoskeletal Disorders, 2012)
Abstract Background Dupuytren’s contracture (DC) is a progressive fibroproliferative disorder characterized by development of nodules and collagen cords within the palmar fascia of the hand. Collagenase clostridium histolyticum (CCH) is currently approved in adults with DC for the nonsurgical treatment of a single palpable cord during a 30-day treatment cycle. This open-label pilot study was designed to examine the safety, efficacy, and multiple-dose pharmacokinetics of injecting two cords (affected joints) with multiple doses of CCH concurrently into the same hand in subjects with DC and multiple contractures. Methods Twelve subjects with DC were enrolled, each with ≥3 contractures caused by palpable cords. Efficacy assessments were taken 30 days after treatment and adverse events (AEs) were recorded throughout. In the first treatment period, all subjects were injected with a single dose of CCH (0.58 mg) into a single cord. The same subjects entered a second treatment period 30 days later, where two different cords (affected joints) were injected concurrently on the same hand. A finger extension procedure was performed 24 hours after each administration of CCH to disrupt the enzymatically weakened cord. Results For metacarpophalangeal (MP) joints, mean contracture reduction per joint treated was 29.0 ± 20.7 degrees following single injection vs 30.3 ± 10.9 degrees per treated joint following multiple injections. For proximal interphalangeal (PIP) joints, mean reduction in contracture was 30.7 ± 21.1 and 22.1 ± 4.9 degrees per treated joint, respectively, for the two periods. All patients (100%) were either “quite satisfied” or “very satisfied” following either treatment cycle. The most common treatment-related AEs were edema peripheral, contusion, and pain in the treated extremity; the differences in severity for local effects of the injections were minimal between treatment periods. No serious treatment-related AEs or systemic complications were reported. Conclusion These results provide preliminary evidence that two cords (affected joints) can be treated concurrently with CCH with similar efficacy and safety as cords treated individually in a sequential fashion. Multiple concurrent injections would eliminate the 30-day wait between single treatments and allow for rapid and effective treatment of patients with multiple affected joints, a significant advantage for both patient and physician. Trial registration Australian New Zealand Clinical Trials Registry #ACTRN12610001045000.